Implemetasi Pendidikan Islam Anti Ekstremisme Dalam Merajut Harmoni Kabupaten Jember (Studi Kasus Di Aisyiyah Kabupaten Jember): Pendidikan Islam Anti Ekstremisme Dalam Merajut Harmoni - rusdiyanto rusdiyanto; Hairul Huda; Ahmad Nur Mahfuda (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The phenomenon of extremism has spread to all corners of the world, including Indonesia. This is marked by the rampant acts of terror that have hit Indonesia in recent years. As the results of the student tolerance survey Indonesia conducted by Setara Institute in 2016 concluded that 35.7% of students have a new understanding of intolerance at the level thought, 2.4% percent have shown deep intolerance actions and words, and 0.3% have the potential to become terrorists. This survey conducted on 760 respondents who are studying high school country in Jakarta and Bandung, West Java. Surveys from the Wahid Institute and PPIM also shows a similar worrying trend This research is a field research with a qualitative approach. Methods of data collection is done through interviews, observation and documentation. The data obtained were analyzed deductively so as to find research conclusions. The results of the study show that in implementing anti-radicalism Islamic education are as follows: Guiding the Ummah, Conveying religious messages, Establishing cooperation with various parties. For this reason, anti-radicalism Islamic education must continue to be implemented with the steps that need to be taken to implement anti-extremism Islamic education, including: Active preaching and upholding true Islamic teachings, Islamic studies and their development, protection and defense of Muslims. According to 'Aisyiyah, anti-radicalism Islamic education needs to be implemented in society so that; The community understands the true nature of the Islamic religion, the community can have noble morals as exemplified by the Prophet SAW, respect each other, understand differences, and have a high sense of humanity, peace that will continue to be maintained among fellow creatures of Allah, and the Unitary State of the Republic of Indonesia